Environmental pesticide exposure modulates cytokines, arginase and ornithinedecarboxylase expression in human placenta - Bulgaroni, Vanina (2013)
To evaluate the cytokine balance and enzymatic alterations induced by environmental pesticide exposure during pregnancy, this transversal study explored placentas derived from non-exposed women (control group-CG), and from women living in a rural area (rural group-RG), collected during intensive organophosphate (OP) pesticide spraying season (RG-SS) and during non-spraying season (RG-NSS). The exposure biomarkers blood cholinesterase and placental carboxylesterase (CaE) were significantly decreased in RG-SS. Among the cytokines studied IL-8, IL-6, TNF, IL-10, TGF and IL-13, the expression frequency of IL-13 increased in RG-SS. Arginase and ornithine decarboxylase (ODC) enzymes were induced in syncytiotrophoblast and endothelial cells. Interestingly, the decrease in CaE activity was associated with arginase and ODC activity induction. These findings suggest that environmental pesticide exposure impacts the placenta by increasing the expression frequency of the anti-inflammatory cytokine IL-13, which may be related to the up-regulation of enzymes implicated in tissue repair.